2005
DOI: 10.1039/b508748a
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of CO2 with sodium-promoted W(011)

Abstract: The activation of CO2 by interaction with Na atoms on tungsten was studied in a joint experimental/theoretical effort combining MIES, UPS (HeII) and first principles calculations. Experimentally, both the adsorption of Na on tungsten, followed by CO2 exposure to the Na-modified surface at 80 K, and the adsorption of CO2 on tungsten, followed by Na exposure to the CO2 covered substrate, were studied. Below about 120 K CO2 physisorbs on pure W(011), and the distance between the three main spectral features is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
(39 reference statements)
1
12
0
Order By: Relevance
“…The latter generally implies a catalyst which activates CO 2 through a charge transfer mechanism leading to a highly bent adsorbed molecule. This can be achieved, for instance, through co-adsorption with an alkali metal on a metal surface [8,9], or the catalytic activation by transition metal catalysts with multiple redox states [10].…”
Section: Introductionmentioning
confidence: 99%
“…The latter generally implies a catalyst which activates CO 2 through a charge transfer mechanism leading to a highly bent adsorbed molecule. This can be achieved, for instance, through co-adsorption with an alkali metal on a metal surface [8,9], or the catalytic activation by transition metal catalysts with multiple redox states [10].…”
Section: Introductionmentioning
confidence: 99%
“…4 This is, however, a challenging process because CO 2 is extremely stable and most often interacts only weakly with many surfaces. Activation may be achieved by adding promoters to an otherwise inactive surface 5 or by making use of more reactive catalytic materials. In this respect, a significant number of studies have been reported in the literature on the CO 2 adsorption, activation, and conversion on metals, 6,7 metal-oxides, 8,9 and metal organic frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…non-spontaneous under mild conditions and additional energy/pressure is required to enhance such contact in most of the common materials. Improved strategies have been investigated by Illas and co-workers when interacting CO 2 with cations 15 and novel transition metal carbide materials. 16 Also, Meng et al show that the use of alkali reagents to modify the surface of TiO 2 increases CO 2 adsorption, and also activates the subsequent conversion.…”
Section: Introductionmentioning
confidence: 99%